2022
DOI: 10.1371/journal.pone.0266944
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism (VTE) prevention and diagnosis in COVID-19: Practice patterns and outcomes at 33 hospitals

Abstract: Background Early reports of increased thrombosis risk with SARS-CoV-2 infection led to changes in venous thromboembolism (VTE) management. Real-world data on the prevalence, efficacy and harms of these changes informs best practices. Objective Define practice patterns and clinical outcomes related to VTE diagnosis, prevention, and management in hospitalized patients with coronavirus disease-19 (COVID-19) using a multi-hospital US sample. Methods In this retrospective cross-sectional study of 1121 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…Studies have con rmed that infection with SARS-CoV-2 can induce a massive thrombotic state [41][42][43]. We have also observed this phenomenon, and clinicians at our dialysis center found that even when receiving anticoagulant doses (1000-3000IU) of low molecular weight heparin, some patients still found that intravenous pot dialyzer tubing developed during dialysis.…”
Section: Laboratory Indicatorssupporting
confidence: 54%
“…Studies have con rmed that infection with SARS-CoV-2 can induce a massive thrombotic state [41][42][43]. We have also observed this phenomenon, and clinicians at our dialysis center found that even when receiving anticoagulant doses (1000-3000IU) of low molecular weight heparin, some patients still found that intravenous pot dialyzer tubing developed during dialysis.…”
Section: Laboratory Indicatorssupporting
confidence: 54%
“…Nevertheless, three cohorts and one cross-sectional study implied no role for post-discharge thromboprophylaxis [ 20 , 23 25 ]. Additionally, three cohort studies did not provide a definite opinion on this matter [ 26 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have confirmed that infection with SARS-CoV-2 can induce a massive thrombotic state [ 41 – 43 ]. We have also observed this phenomenon, and clinicians at our dialysis center found that even when receiving anticoagulant doses (1000-3000IU) of low molecular weight heparin, some patients still found that intravenous pot dialyzer tubing developed during dialysis.…”
Section: Discussionmentioning
confidence: 99%